Mutation analysis of TCOF1 gene in Chinese Treacher Collins syndrome patients. Issue 1 (9th September 2020) - Zhang, Chuan; An, Lisha; Xue, Huiqin; Hao, Shengju; Yan, Yousheng; Zhang, Qinghua; Jin, Xiaohua; Li, Qian; Zhou, Bingbo; Feng, Xuan; Ma, Panpan; Wang, Xing; et al.
Abstract: Background: Treacher Collins syndrome (TCS) is a rare autosomal dominant or recessive disorder, that involves unique bilateral craniofacial malformations. The phenotypes of TCS are extremely diverse. Interventional surgery can improve hearing loss and facial deformity in TCS patients. Method: We recruited seven TCS families. Variant screening in probands was performed by targeted next‐generation sequencing (NGS). The variants identified were confirmed by Sanger sequencing. The pathogenicity of all the mutations was evaluated using the guidelines of the American College of Medical Genetics and Genomics (ACMG) and InterVar software. Results: Three frameshift variants, two nonsense variants, one missense variant, and one splicing variant of TCOF1 were identified in the seven TCS probands. Five variants including c.1393C > T, c.4111 + 5G>C, c.1142delC, c.2285_2286delCT, and c.1719delG had not been previously reported. Furthermore, we report the c.149A > G variant for the first time in a Chinese TCS patient. We provided prenatal diagnosis for family 4. Proband 7 chose interventional surgery. Conclusion: We identified five novel variants in TCOF1 in Chinese patients with TCS, which expands the mutation spectrum of TCOF1 in TCS. Bone conduction hearing rehabilitation can improve hearing for TCS patients and prenatal diagnosis can provide fertility guidance for TCS families. Abstract : Figure 1. The facial features of these patients are characteristic of TCS. Figure 2. Sanger sequencing of TCOF1 : P is proband, F is father, M is mother, AF is amniotic fluid. None of the parents of these seven families detected the same variation as the proband had. The Sanger sequencing of fetus for family 4 was normal